Perceived Support, Language Learning Motivation and Oral Performance Among Freshmen College Students - Libas, Sem; Macatangay, Mia Carla; Casaway, Aiza; Pujanes, Vinzyrah; Jallorina, Alma; Galicia, Leomar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationships among perceived support system, language learning motivation, and self-confidence in oral performance among teacher education students in selected private higher education institutions in Laguna and Cavite, Philippines. Anchored on Vygotsky’s Sociocultural Theory, Gardner’s Socio-Educational Model, Ryan and Deci’s Self-Determination Theory, and Bandura’s Self-Efficacy Theory, the study investigated how social support and language learning motivation contribute to students’ confidence in oral communication. A quantitative, descriptive-correlational research design was employed involving 200 teacher education students selected through stratified random sampling. Data were collected using a validated researcher-made questionnaire consisting of 35 items, and descriptive statistics, Pearson’s correlation coefficient, and multiple linear regression analysis were used for data analysis. The findings revealed that respondents demonstrated a strong perceived support system, a very high level of language learning motivation, and a very high level of self-confidence in oral performance. Teacher support emerged as the strongest source of perceived support, followed by peer support, while family support showed the least influence. Significant positive relationships were found among perceived support system, language learning motivation, and self-confidence in oral performance. Furthermore, both perceived support system and language learning motivation significantly predicted self-confidence in oral performance, with language learning motivation identified as the stronger predictor. The findings underscore the importance of fostering supportive learning environments and strengthening students’ motivation to enhance oral communication confidence. Educational institutions are encouraged to promote positive teacher–student relationships, peer collaboration, and meaningful communication activities that reinforce students’ intrinsic motivation and confidence in oral performance. The study supports Sustainable Development Goal (SDG) 4: Quality Education and SDG 8: Decent Work and Economic Growth by promoting communication competence, confidence, and professional readiness among future educators. The findings also contribute to educational, institutional, community, and socio-economic sustainability by providing evidence to guide learner-centered interventions that strengthen motivation, confidence, and oral communication competence.
Keywords: Language Learning Motivation; Oral Communication; Perceived Support System; Self-Confidence; Teacher Education Students